Optimization of culture conditions for gamma-aminobutyric acid production by newly identified Pediococcus pentosaceus MN12 isolated from 'mam nem', a fermented fish sauce. Issue 1 (1st January 2021) - Thuy, Do Thi Bich; Nguyen, An Tien; Khoo, Kuan Shiong; Chew, Kit Wayne; Cnockaert, Margo; Vandamme, Peter; Ho, Yeek-Chia; Huy, Nguyen Duc; Cocoletzi, Heriberto Hernández; Show, Pau Loke
ABSTRACT: This study was aimed to identify and optimize the culture conditions for gamma-aminobutyric acid (GABA) production by a lactic acid bacterium strain isolated from mam nem, a fermented fish sauce. Among the six isolates obtained from mam nem, the MN12 had the most potent GABA-producing capability. The strain was then identified to be Pedioccocus pentosaceus by employing MALDI-TOF-MS and phenylalanyl-tRNA synthase sequencing methods. The initial cell density of 5.10 6 CFU/mL, monosodium glutamate concentration of 60 mM, initial pH of 7, temperature of 45°C and cultivation time of 72 h were found to be the optimal culture conditions for highest production of GABA, reaching 27.9 ± 0.42 mM, by this strain. The cultivation conditions for GABA production by P. pentosaceus MN12 have been successfully optimized, providing a foundation for the development of fermented foods enriched with GABA. Graphical Abstract: uf0001